Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The impact of the culture of volunteer work on the behavior of male and female students  in public schools in the city of AbhaMrs. Shadiah Naser Al Majthel2. Circulation of individual and collective theoretical supervisory methods  in educational supervisory workMrs. Ibtihaj A. Al-Bakri3. The Statues of Job Enrichment among Public School Principals in Hebron Governorate  from the teachers' point of viewMrs. Tagreed Yaser Awawdeh, Dr. Ashraf Mohammad Abu Khayran4. The Trend towards Specialization and its Relationship to the Anxiety of the Professional future among special education students at Tafila Technical UniversityMrs. Hadeel Mohammed Al-Hawamdeh, Mrs. Ibtihal Mohammad Al-Khrissat5. Emotional Intelligence and its Relationship to Life Satisfaction among Secondary School Female Students in Hail regionMrs. Amani Abdullah Aqla Al-Shammari6. An Integrative approach to treating porn addictionDr. Heba Jamal Hariri
Keywords: Journal of Educational and Psychological Sciences